Gene expression variations and allele-specific expression of two rice and their hybrid in caryopses at single-nucleus resolution - Zhou, Han; Deng, Xing Wang; He, Hang (Frontiers in Plant Science, 2023)
Seeds are an indispensable part of the flowering plant life cycle and a critical determinant of agricultural production. Distinct differences in the anatomy and morphology of seeds separate monocots and dicots. Although some progress has been made with respect to understanding seed development in Arabidopsis, the transcriptomic features of monocotyledon seeds at the cellular level are much less understood. Since most important cereal crops, such as rice, maize, and wheat, are monocots, it is essential to study transcriptional differentiation and heterogeneity during seed development at a finer scale. Here, we present single-nucleus RNA sequencing (snRNA-seq) results of over three thousand nuclei from caryopses of the rice cultivars Nipponbare and 9311 and their intersubspecies F1 hybrid. A transcriptomics atlas that covers most of the cell types present during the early developmental stage of rice caryopses was successfully constructed. Additionally, novel specific marker genes were identified for each nuclear cluster in the rice caryopsis. Moreover, with a focus on rice endosperm, the differentiation trajectory of endosperm subclusters was reconstructed to reveal the developmental process. Allele-specific expression (ASE) profiling in endosperm revealed 345 genes with ASE (ASEGs). Further pairwise comparisons of the differentially expressed genes (DEGs) in each endosperm cluster among the three rice samples demonstrated transcriptional divergence. Our research reveals differentiation in rice caryopsis from the single-nucleus perspective and provides valuable resources to facilitate clarification of the molecular mechanism underlying caryopsis development in rice and other monocots.